Investigação de atividades biológicas e potencial uso de extratos das flores de acácia mearnsii obtidos por arraste a vapor e extração com fluido supercrítico - Silva, Graciane Fabiela da (2018)
Although the Acacia mearnsii tree is widely cultivated and used in the industry, its flowers are seldom researched. Considering the extensive availability of A. mearnsii flowers and the growing interest in natural products, this work aimed at the obtainment of extracts from these flowers and investigation of their composition and biochemistry properties. In this work, essential oil and aqueous extract by steam distillation and extracts were obtained with supercritical fluid. The essential oil was characterized by CG-MS and olfactometry. The main compounds identified in the essential oil were 8-heptadecene, heptadecane, nonadecane e kaurene. The main aroma detected by olfactometric analysis was roast nutty, as well as coffee, sweet, floral, vegetal and spicy. Antioxidant activity was determined and the aqueous extract showed an activity superior to rutin standard. LC-qTOF-MS identified 42 likely phenolic compounds, such as quercitrin, naringenin, myricetin, rutin, and robinetin. The extracts obtained by supercritical extraction and isolated fractions presented activity against S. aureus. The yield of the supercritical extraction was optimized using factorial planning and mass transfer parameters were obtained through mathematical models that represent the extraction curve. Thus, it was concluded that the flowers of A. mearnsii can be exploited by extractive processes used in this study to generate a plant by-product. The results indicate the aromatic and antioxidant potential of the essential oil and aqueous extract, respectively, obtained with 2.0 bar steam distillation, while the supercritical extract has antibacterial action.